Pengaruh Peningkatan Jumlah Uang Beredar Dan Harga Bbm Terhadap Inflasi Indonesia Periode Januari 2005 - Agustus 2008 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRAKSI Monthly inflation rate in Indonesia these days raced by growth of amount of money supplies and oil price. Hence from that is this article studies improvement money supply and oil price to Inflation in Indonesia. Model log-linear three variables is adopting from function of produce of CobbDauglas applied in this research. From this research yielded level of improvement influence elasticity of money supply and oil price to inflation. The result can be applied government as benchmark in taking public policy about increase of oil fuel price and to control money supply.